Development of 21st Century Skills through Project-Based Learning at Al-Azhar 15 Islamic Junior High School Cilacap - Rahayu, Sri (UM Purwokerto Press, 2024)
Education seeks to improve 21st century skills. In facing the challenges of an increasingly complex modern era 21st century skills, such as critical thinking, creativity, collaboration, communication, and digital literacy, are important. The method of this paper uses documentation analysis and literature study on project-based learning and 21st century skills. Data will be collected from various sources such as educational policies, writing reports, and related scientific publications. The results of this paper are expected to provide a better understanding of the development of 21st century skills through project-based learning. the conclusion of this paper, it is expected to find ways that can be used to develop 21st century skills in education. The implications of this writing are expected to provide valuable input for educators to be able to develop 21st century skills through projects created and educators can design and implement curriculum that supports the development of 21st century skills well.